2011
DOI: 10.1111/j.1528-1167.2011.03134.x
|View full text |Cite
|
Sign up to set email alerts
|

A retrospective population‐based study on seizures related to childhood vaccination

Abstract: Summary Purpose:  Cases of severe childhood epilepsies in temporal association with vaccination have great impact on the acceptance of vaccination programs by parents and health care providers. However, little is known about the type and frequency of seizures and epilepsy syndromes following vaccination. This study aims to describe the clinical features of children presenting with seizures after vaccination using a register‐based cohort. Methods:  We surveyed the national German database of adverse events foll… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
14
1
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 43 publications
1
14
1
1
Order By: Relevance
“…10 In our study, West syndrome was a much less frequently identified epilepsy syndrome after vaccination, in contrast to another study, 18 probably because we used strict criteria for a temporal relation between vaccination and seizures.…”
Section: Figurecontrasting
confidence: 64%
See 1 more Smart Citation
“…10 In our study, West syndrome was a much less frequently identified epilepsy syndrome after vaccination, in contrast to another study, 18 probably because we used strict criteria for a temporal relation between vaccination and seizures.…”
Section: Figurecontrasting
confidence: 64%
“…13,14 The detection of a pathogenic SCN1A mutation in children with alleged vaccination encephalopathy proved that, although the vaccination might have triggered the first seizure, the epilepsy and subsequent intellectual disability were caused by a genetic defect. 10 Most published case series and retrospective cohort studies confirming SCN1A-related Dravet syndrome as a cause of alleged vaccination encephalopathy [15][16][17][18] have focused on epileptic encephalopathy. Only a few case reports have shown that occasionally other genetic causes of epilepsy also present with seizures after vaccination.…”
Section: Discussionmentioning
confidence: 99%
“…4,37 It is a matter for debate whether the choice of separate versus combination vaccine is a policy decision or a choice for parents to make in consultation with their vaccination provider. If MMRV continues to be offered for first-dose administration, it might be advisable to counsel parents regarding antipyretic use if children experience a fever within the peak risk period.…”
Section: Resultsmentioning
confidence: 99%
“…Bei gehäuften Anfällen oder während einer medikamentösen Umstellung sollte eine nicht unbedingt erforderliche Impfung sicherheitshalber zurückgestellt werden. Bei Kindern mit epileptischen Fieberanfällen (Fieberkrämpfen) in der Vorgeschichte kann bei solchen Impfungen, die häufig mit einer fieberhaften Allgemeinreaktion einhergehen, vorsorglich eine Gabe fiebersenkender Medikamente (Paracetamol) erfolgen und gegebenenfalls ein Medikament zum Abbruch länger andauernder Anfälle bereitgehalten werden [5].…”
Section: Dieter-janz-preisunclassified